HUMAN CAPITAL IN THE BANKING SECTOR CROSS CULTURAL DEFINITION - Perera, A. (University of Jaffna, 2018)
Businesses around the world proclaim their employees as being the corporation’s most valuable resource. The field of human capital (HC) is not a new one and, studies focussing specifically on HC and its importance to organisations have been published in the academic press for several decades (Amit & Zott, 2001; Barney & Wright, 1998; Otoo & Mishra, 2018; Wernerfelt, 1984). However, despite continuous research attention, HC remains underdeveloped and an under- researched concept (Gambardella, Panico, & Valentini, 2015; Lewis & Heckman, 2006; McDonnell, 2011). Specially, there is an absence of uniformity in the meanings of term human capital, thus, this exploratory research inquired from those who make use of the concept to define it. Research methods will include interviews with 10 banks in Sri Lanka and New Zealand and secondary sources. Data analysis was carried out using content analysis. The findings revealed that there is a greater likelihood of banks in both countries defined the term HC in a similar way to a greater extent though the differences exist. The findings further, offered an insight for future investigations on how the definition of a developing country differ from that of a developed country.
Keywords: definition; banks; human capital; New Zealand; Sri Lanka